2017
DOI: 10.1530/eje-16-0835
|View full text |Cite
|
Sign up to set email alerts
|

Contact system activation and high thrombin generation in hyperthyroidism

Abstract: This study demonstrated that contact system activation and abundant NET formation occurred in the high thrombin generation state in hyperthyroidism and were correlated with free T4 level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…However, as exogenous hyperthyroidism in healthy volunteers had no effect on any of the clot structure parameters, additional mechanisms for the effects on hemostasis observed in healthy volunteers using levothyroxine must be present. The final study demonstrated that contact system activation and abundant neutrophil extracellular trap formation occurred in the high thrombin generation state in hyperthyroidism and were correlated with FT 4 level .…”
Section: Discussion and Concluding Remarksmentioning
confidence: 82%
“…However, as exogenous hyperthyroidism in healthy volunteers had no effect on any of the clot structure parameters, additional mechanisms for the effects on hemostasis observed in healthy volunteers using levothyroxine must be present. The final study demonstrated that contact system activation and abundant neutrophil extracellular trap formation occurred in the high thrombin generation state in hyperthyroidism and were correlated with FT 4 level .…”
Section: Discussion and Concluding Remarksmentioning
confidence: 82%
“…Most coagulation abnormalities associated with thyroid disease are the result of direct effects of thyroid hormones on the synthesis of various hemostatic factors or disorders of immune function [15]. Hypercoagulable states had been reported in patients with hyperthyroidism, and patients with moderate hypothyroidism have an in-creased risk of thrombosis, as opposed to bleeding tendencies in patients with severe hypothyroidism [24][25][26]. A hypercoagulable state has also been described in patients with thyroid cancer .…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that more than 50% of ALF patients exhibit abnormal thyroid parameters, and their prognosis was worse than that of normal thyroid patients (Anastasiou et al, 2015). In addition, a study suggested that hyperthyroidism was associated with an increased risk of thrombosis, and patients with hyperthyroidism show higher levels of fibrinogen (Kim et al, 2017). Another study confirmed that VWF and fibrinogen mediate up to 10% of the association between FT4 and cardiovascular disease (Bano et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying novel and overlooked biomarkers, which not only guide the diagnosis and prognosis of patients with CAD but also detect new molecular mechanisms to elucidate the pathological progress of CAD, is important due to the limited predictive power of few predictors based on genetic factors and traditional clinical risk biomarkers available for risk stratification in patients with CAD. Hyperthyroidism is linked to an increased risk of thrombus (Kim et al, 2017). Data from epidemiological studies indicate that patients with low thyroid hormone levels are at higher risk of heart failure, and the prognosis of heart failure is also worse (Vale et al, 2019).…”
Section: Introductionmentioning
confidence: 99%